Influence of decreasing minisett weight and intra-row spacing on the coated ginger cv Taffin-giwa - OKWUOWULU, P A (Journal of Spices and Aromatic Crops, 1992)
The influence of varying minisett weights, intra-row spacing, sites and weather on yield of the ginger cv. Taffin giwa is discussed. Yield of fresh ginger at increasing miniseH weights has the same effects as decreasing intra-row spacing, both factors ihversely related to seed harvest multiplication ratio. Off-shoots (seed pieces = 3g) are potential setts. Using reduced minisetts stimulates complete hamessing of food reserve in mother setts during crop growth. The level of sunshine and heat radiation during crop growth and drastiderratic changes in ambient soil temperature in the tuberous stem deposition zone cause significant (< 30%) yield losses.